2020
DOI: 10.1002/ange.201913958
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Assembly of Nano‐architectures through Designing Anisotropic DNA Origami Patches

Abstract: Programmable assembly of nanoparticles (NPs) into well‐defined architectures has attracted attention because of tailored properties resulting from coupling effects. However, general and precise approaches to control binding modes between NPs remain a challenge owing to the difficulty in manipulating the accurate positions of the functional patches on the surface of NPs. Here, a strategy is developed to encage spherical NPs into pre‐designed octahedral DNA origami frames (DOFs) through DNA base‐pairings. The DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…However, unlike atoms with precise bond geometries and binding energies, assembly of macromolecules or colloidal building blocks into single crystals with designable crystalline morphologies remains a great challenge. DNA origami frames are sometimes treated as analogues of atoms 11 17 , because the shapes of the structures and the functional sites on them can be well-controlled by design 18 30 . Moreover, colloidal-sized particles and proteins can be precisely encaged by these DNA frames 21 , 25 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike atoms with precise bond geometries and binding energies, assembly of macromolecules or colloidal building blocks into single crystals with designable crystalline morphologies remains a great challenge. DNA origami frames are sometimes treated as analogues of atoms 11 17 , because the shapes of the structures and the functional sites on them can be well-controlled by design 18 30 . Moreover, colloidal-sized particles and proteins can be precisely encaged by these DNA frames 21 , 25 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…DNA origami technology, benefiting from its structural programmability, provides a powerful toolbox to position or encapsulate guest molecules or NPs with nanoscale precision or within 3D scaffold. , On the other hand, crystallization of DNA structures with well-defined shapes allows one to rationalize the assembly of specific lattice types. It has been demonstrated that lattices with designed organizations of DNA motifs in templated lattices can exhibit novel photonic properties . Although a massive progress has been achieved in this regard, the tailorable accommodation of guest species inside DNA frames is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2,[15][16][17][18] So far, a variety of DNA structures including thiolated DNA, spherical nucleic acids, DNA tiles, DNA origami and DNA patches have served as the sticky "glue" for nanoparticles for valence engineering of PANs. [19][20][21][22][23][24] Analogous to the valence bonds of atoms, these DNA structures confer nanoparticles with specic chemical or topological properties. Despite these elegant features, assembly of PANs with high valences and high yields remains a grand challenge in current synthetic systems due to the small size of nanoparticles (normally 5-20 nm), random DNA arrangements around each nanoparticle and uncontrollable aggregation of nanoparticles in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%